PERIRENAL HEMATOMA AFTER URETEROSCOPY : A SYSTEMATIC REVIEW - Rachmadhyan, Reyhansyah (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The global incidence of urolithiasis is 14%, and the burden of urological consultants has increased by 20% over the past seven years, according to current trends. As a consequence, stone disease is becoming a burden on our health care system. However, advancements in apparatus and technology over the past two decades have made it possible for endourologists to perform increasingly complex treatments for the management of stones. Endourologists who treat ureteral or renal calculi are required to be aware of PRH risk factors. PRH occurred more frequently among patients with a low BMI. Patients with a low BMI had less body fat and perirenal fat than those with a higher BMI. After an injury, perirenal fat cushions the kidney to prevent cortical overstretching caused by an increase in renal pelvis irrigation pressure. PRH is produced in kidneys with minimal perirenal adipose. Two of the four patients with PRH had a low BMI. Underweight can be a sign of malnutrition, which can impair the structure of the kidneys. The timing of surgery is uncertain. PRH caused by FURSL may be treated as a kidney injury. If the patient has loin or flank pain after FURSL, the surgeon should examine the serum hemoglobin and perform abdominal sonography or a CT scan to detect PRH. Hematomas with mass effect were evacuated percutaneously when they were large. Percutaneous drainage may delay the progression of a hematoma in stable patients, although it may cause severe discomfort or renal compression. Angiograms should be used to treat renal bleeding if the serum hemoglobin continues to decline. If conservative or angiographic therapy fails to control bleeding, immediate open surgery must be performed. Cases of PRH are extremely uncommon, with percentages ranging from 0.1 to 8.9%. Despite this, this condition needs to be monitored closely because it has the potential to compromise the patient's health in a negative way.